Food systems transformations in South America: Insights from a transdisciplinary process rooted in Uruguay - Juri, Silvana; Baraibar, Matilda; Clark, Laurie Beth; Cheguhem, Mauricio; Jobbagy, Esteban; Marcone, Jorge; Mazzeo, Néstor; Meerhoff, Mariana; Trimble, Micaela; Zurbriggen, Cristina; Deutsch, Lisa (Frontiers in Sustainable Food Systems, 2022)
The wicked nature of sustainability challenges facing food systems demands intentional and synergistic actions at multiple scales and sectors. The Southern Cone of Latin America, with its historical legacy of “feeding the world,” presents interesting opportunities for generating insights into potential trajectories and processes for food system transformation. To foster such changes would require the development of collective understanding and agency to effectively realize purposeful and well-informed action toward desirable and sustainable food futures. This in turn demands the transdisciplinary engagement of academia, the private sector, government/policy-makers, community groups, and other institutions, as well as the broader society as food consumers. While the need for contextualized knowledge, priorities and definitions of what sustainable food systems change means is recognized, there is limited literature reporting these differences and critically reflecting on the role of knowledge brokers in knowledge co-production processes. The political nature of these issues requires arenas for dialogue and learning that are cross-sectoral and transcend knowledge generation. This paper presents a case study developed by SARAS Institute, a bridging organization based in Uruguay. This international community of practice co-designed a 3-year multi-stakeholder transdisciplinary process entitled “Knowledges on the Table.” We describe how the process was designed, structured, and facilitated around three phases, two analytical levels and through principles of knowledge co-production. The case study and its insights offer a model that could be useful to inform similar processes led by transdisciplinary communities of practice or bridging institutions in the early stages of transformative work. In itself, it also represents a unique approach to generate a language of collaboration, dialogue, and imagination informed by design skills and methods. While this is part of a longer-term process toward capitalizing on still-unfolding insights and coalitions, we hope that this example helps inspire similar initiatives to imagine, support, and realize contextualized sustainable food system transformations.